IMPLEMENTASI SISTEM DRAINASE PERKOTAAN DI KAWASAN PERUMNAS III KELURAHAN TANJUNG HULU KECAMATAN PONTIANAK TIMUR - Ika Muthya Anggraini; Ir. Zainal Wahyu; Muji Listyo Widodo; Temmy Hastian (Politeknik Negeri Sriwijaya, 2022)
The Perumnas III Complex is one of the residential areas in the Tanjung Hulu Village, East Pontianak District. The main problem in the housing area of ​​Perumnas III, especially RW 09, Tanjung Hulu Village, East Pontianak District, is that it is vulnerable to flooding during the rainy season. This condition will get worse when high tide occurs. Drainage channels are no longer able to accommodate high rainfall. The efficiency of the existing line has been reduced. Sedimentation and garbage that clog causes the flow of water can not flow optimally and smoothly. The daily activities of residents are disrupted and the environment becomes unhealthy. Based on the background of these problems, residential areas require real knowledge and action in the implementation of making good drainage. The purpose of this PKM implementation will be to provide education to the community and examples of drainage modeling to be applied in the residential area. The method used in this PKM is the lecture/discussion method, and the demonstration method. The results of this PKM activity are expected to increase the knowledge of residents after socializing the urban drainage system, Operation-Maintenance (OP) of drainage channels and Clean and Healthy Life Behavior (PHBS). This PKM activity will also produce examples of drainage modeling to be applied in the residential area of ​​Perumnas III, especially RW 09.